A composite rare earth silicate-rare earth zirconate gradient structure ultra-high temperature thermal / environmental barrier coating and preparation method thereof
By preparing composite rare earth silicate-rare earth zirconate gradient structure coating on ceramic matrix composites, the problem of degradation of the protection effect of existing high-temperature environmental barrier coatings at high service temperatures is solved, and a higher service temperature and longer thermal cycle life is achieved.
Patent Information
- Application Number
- CN202411794069.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-09
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2044-12-09
AI Technical Summary
The protective effect of the existing high-temperature environmental barrier coatings has significantly decreased at higher service temperatures, and there are problems such as low temperature bearing capacity, mismatch of thermal expansion and SiO2 volatility.
Atmospheric plasma spraying technology is used to prepare Si bonding layer, RE2Si2O7 intermediate layer, RE2SiO5-RE2Si2O7 transition layer and rare earth zirconate insulation top layer on the ceramic matrix composite material to form a composite rare earth silicate-rare earth zirconate gradient structure ultra-high temperature thermal/environmental barrier coating.
It improves the service temperature of hot end components of ceramic matrix composite materials, enhances the coating's resistance to high-temperature water-oxygen corrosion and sintering resistance, alleviates the problem of thermal expansion mismatch, and extends the thermal cycle life of the coating.
Smart Images

Figure CN119241282B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of high-temperature protective coatings, and in particular to a novel composite rare earth silicate-rare earth zirconate gradient structure ultra-high temperature thermal / environmental barrier coating and a preparation method thereof. Background Art
[0002] Silicon carbide ceramic composites are considered to be one of the ideal high-temperature structural materials for the hot end components of advanced gas turbine engines (aeroengines and heavy-duty gas turbines) due to their low density, high specific strength, excellent high-temperature resistance and oxidation resistance, and good high-temperature creep resistance. However, in practical applications, these components face severe challenges such as high-temperature water-oxygen corrosion and molten salt corrosion, which lead to rapid attenuation and failure of their coatings and composite matrix, greatly reducing their service life. Environmental barrier coatings (EBCs) can effectively isolate corrosive media such as water vapor and molten salts, slow down or prevent the reaction of ceramic matrix materials with high-temperature water vapor, molten salts, etc., and thus improve the service life of hot end components. Therefore, the development of excellent performance environmental barrier coating materials and coating structure system design, combined with appropriate preparation processes, has become one of the hot spots in the current research on high-performance environmental barrier coatings.
[0003] Rare earth silicate materials have low thermal expansion coefficient, high temperature bearing capacity, good phase stability and chemical compatibility. Based on the long life and excellent comprehensive performance of rare earth silicates, the Si / Mullite / RE Silicates environmental barrier coating system composed of Si bonding layer, mullite intermediate layer and rare earth silicate surface layer is one of the most widely studied and applied high-temperature protective coating systems. At present, the most commonly used bonding layer material for environmental barrier coating systems is silicon (Si), which is mainly due to the advantages of Si and silicon carbide substrate having similar thermal expansion coefficients and good chemical compatibility. However, the melting point of Si is 1414℃, which will be greatly reduced in the presence of impurities. This limits the use temperature of the EBCs system to the environmental barrier layer / bonding layer interface temperature of about 1350℃ or lower. However, as gas turbine engines develop towards high thrust-to-weight ratio, high thermal efficiency, high environmental protection and low fuel consumption, the inlet temperature of the gas turbine engine turbine continues to increase, and advanced environmental barrier coatings face higher service temperature assessments, which puts higher requirements on the temperature bearing capacity and thermal insulation performance of the coating.
[0004] Faced with the complex environment and higher gas temperature in the combustion chamber of advanced gas turbine engines, the protective effect of EBCs has been significantly reduced. In order to further improve the overall performance of the engine and combine the concept of thermal barrier coatings, thermal / environmental barrier coatings (T / EBCs) were proposed, that is, on the basis of the original environmental barrier coating, thermal insulation function or thermal insulation layer is added to increase the service temperature of the ceramic matrix composite matrix. Therefore, the development of high-performance thermal / environmental barrier coatings that are resistant to high temperatures, have high temperature phase stability, high bonding strength, good interface matching and thermal insulation performance is one of the key core technologies for the development of the next generation of ceramic matrix composite hot end components.
[0005] The traditional classic environmental barrier coating is Si bonding layer / mullite transition layer / Yb2SiO5 top layer, which has the following problems: a. Low temperature bearing capacity, service temperature <1400℃, long-term ≤1350℃; b. There is a thermal expansion mismatch between mullite and Yb2SiO5; c. There is a serious SiO2 volatilization problem during the plasma spraying of Yb2SiO5, resulting in the presence of two phases of Yb2SiO5 and Yb2O3 in the coating.
[0006] In view of the above-mentioned defects, the inventors of the present invention finally obtained the present invention after a long period of research and practice. Summary of the invention
[0007] The purpose of the present invention is to solve the problem of how to improve the service temperature of the hot end components of ceramic-based composite materials, and to provide a novel composite rare earth silicate-rare earth zirconate gradient structure ultra-high temperature thermal / environmental barrier coating and a preparation method thereof.
[0008] In order to achieve the above-mentioned purpose, the present invention discloses a novel composite rare earth silicate-rare earth zirconate gradient structure ultra-high temperature thermal / environmental barrier coating, comprising a Si bonding layer, a RE2Si2O7 intermediate layer, a RE2SiO5-RE2Si2O7 composite rare earth silicate transition layer, and a rare earth zirconate thermal insulation top layer, which are sequentially prepared on a ceramic-based composite material substrate.
[0009] The matrix of the ceramic-based composite material is a silicon carbide fiber reinforced silicon carbide ceramic matrix or a carbon fiber reinforced silicon carbide ceramic matrix.
[0010] The rare earth RE in the RE2Si2O7 intermediate layer is any one of ytterbium and lutetium or a combination of the two, and the molar fraction of RE2Si2O7 is ≥97%.
[0011] The rare earth RE in the RE2SiO5-RE2Si2O7 composite rare earth silicate transition layer is any one of ytterbium and lutetium or a combination of the two. In the RE2SiO5-RE2Si2O7 coating system, the molar ratio of RE2SiO5 to RE2Si2O7 is 0.67-1.5.
[0012] The rare earth zirconate thermal insulation top layer is RE2 (Zr 1-x Y x )2O7, wherein RE is lanthanum or samarium, 0≤x≤0.1.
[0013] The present invention also discloses a method for preparing the novel composite rare earth silicate-rare earth zirconate gradient structure ultra-high temperature thermal / environmental barrier coating, comprising the following steps:
[0014] S1, cleaning the ceramic matrix composite material substrate with alcohol and acetone to remove oil stains on the substrate surface, roughening the substrate with 24-mesh silicon carbide sand blasting, and cleaning the roughened substrate with acetone and anhydrous ethanol as the medium by ultrasonic vibration to remove the sand remaining on the substrate;
[0015] S2, using atmospheric plasma spraying technology to prepare a Si bonding layer on the surface of the ceramic-based composite material substrate roughened in step S1, wherein the thickness of the Si bonding layer is 40-80 μm, and the particle size of the Si spraying powder used is 30-90 μm;
[0016] S3, after the substrate on which the Si bonding layer is sprayed is further coated, an atmospheric plasma spraying technology is used to prepare a RE2Si2O7 intermediate layer, the thickness of which is 50-100 μm. The spraying powder material of the RE2Si2O7 intermediate layer prepared by the plasma spraying technology is (1-x)RE2Si2O7-xSiO2, wherein 0.05≤x≤0.2, and the particle size of the (1-x)RE2Si2O7-xSiO2 composite agglomerated spraying powder material is 15-60 μm;
[0017] S4, on the substrate surface sprayed with Si bonding layer and RE2Si2O7 intermediate layer, atmospheric plasma spraying technology is continued to be used to prepare RE2SiO5-RE2Si2O7 transition layer, the thickness of which is 50-80 μm, the spraying powder material of the transition layer prepared by plasma spraying technology is (1-x)RE2Si2O7-xRE2SiO5, wherein 0.4≤x≤0.5, and the particle size of RE2SiO5-RE2Si2O7 composite agglomerated spraying powder material is 15-60 μm;
[0018] S5, on the surface of the substrate sprayed with RE2SiO5-RE2Si2O7 / RE2Si2O7 / Si coating, atmospheric plasma spraying technology is continued to be used to prepare RE2(Zr 1-x Y x )2O7 top insulation layer, the thickness of which is 100-150 μm, and the RE2(Zr 1-x Y x )2O7 The particle size of the spray powder material of the top insulation layer is 15-60 μm, and RE2(Zr 1-x Y x)2O7 / RE2SiO5-RE2Si2O7 / RE2Si2O7 / Si / ceramic matrix composite material matrix with a new gradient structure ultra-high temperature thermal / environmental barrier coating.
[0019] In the step S2, the process parameters for preparing the Si bonding layer by atmospheric plasma spraying technology are: spraying current is 500-650A, spraying power is 30-35 kW, powder feeding rate is 10-35 g / min, spraying distance is 90-120 mm, main gas flow rate Ar gas is 32-45 L / min, hydrogen flow rate is 2-10 L / min, spray gun moving speed is 500-650 mm / s, and step distance is 3 mm.
[0020] In step S3, the process parameters for preparing the RE2Si2O7 intermediate layer by atmospheric plasma spraying technology are: spraying current is 500-600 A, spraying power is 34-42 kW, powder feeding rate is 20-40 g / min, spraying distance is 90-120 mm, main gas flow rate Ar gas is 32-45 L / min, hydrogen flow rate is 2-12 L / min, spray gun moving speed is 500-650 mm / s, and step distance is 3 mm.
[0021] In step S4, the process parameters for preparing the RE2SiO5-RE2Si2O7 transition layer by atmospheric plasma spraying technology are: spraying current is 500-600 A, spraying power is 34-42 kW, powder feeding rate is 20-40 g / min, spraying distance is 90-120 mm, main gas flow rate Ar gas is 32-45 L / min, hydrogen flow rate is 2-12 L / min, spray gun moving speed is 500-650 mm / s, and step distance is 3 mm.
[0022] In step S5, the atmospheric plasma spraying technology is used to prepare RE2 (Zr 1-x Y x )2O7 The process parameters of the top thermal insulation layer are: plasma spraying power 35~45 kW, spraying distance 85~110 mm, powder feeding rate 20~40 g / min, current 500~650 A, argon flow rate 30~45 L / min, hydrogen flow rate 4~10 L / min, and spray gun moving speed 500~600 mm / s.
[0023] The present invention adopts plasma spraying technology to prepare Si / RE2Si2O7 / RE2SiO5-RE2Si2O7 / rare earth zirconate ultra-high temperature gradient structure thermal / environmental barrier coating system on the surface of ceramic-based composite material matrix, wherein the RE2Si2O7 intermediate layer is in accordance with the stoichiometric ratio, which solves the component segregation caused by the volatilization of SiO2 during the plasma spraying RE2Si2O7 process, and the RE2SiO5-RE2Si2O7 transition layer advantageously alleviates the thermal expansion mismatch problem between RE2Si2O7 and rare earth zirconate at high temperature, which is beneficial to improve the service life of the entire coating system. The rare earth zirconate RE2(Zr 1-x Y x )2O7 (RE = La or Sm, 0 ≤ x ≤ 0.1) The thermal insulation top layer in the coating structure system of the present invention mainly plays a role in thermal insulation. 1-x Y x )2O7 also has good high temperature phase stability, low thermal conductivity, low thermal expansion coefficient, and good high temperature stability and chemical compatibility with the RE2SiO5-RE2Si2O7 transition layer.
[0024] Compared with the prior art, the beneficial effects of the present invention are:
[0025] 1. The RE2Si2O7 intermediate layer in the gradient structure ultra-high temperature thermal / environmental barrier coating system of the present invention is in accordance with the stoichiometric ratio, which solves the problem of component segregation caused by the volatilization of SiO2 during the plasma spraying RE2Si2O7 process, and avoids the generation of new RE2Si2O7 phase and thermal stress at the interface between Si and RE2Si2O7 in the existing Si / RE2Si2O7 environmental barrier coating under high temperature service. Because a large amount of RE2SiO5 is generated during the plasma spraying RE2Si2O7 process, RE2Si2O7 is generated at the interface between Si and RE2SiO5 at high temperature, accompanied by growth thermal stress, which will cause the initiation and expansion of cracks in the coating;
[0026] 2. The RE2SiO5-RE2Si2O7 transition layer in the ultra-high temperature thermal / environmental barrier coating system of the present invention has good sintering resistance and high temperature phase stability at 1400-1500°C, and also has high fracture toughness. The RE2SiO5-RE2Si2O7 transition layer advantageously alleviates the thermal expansion mismatch problem between RE2Si2O7 and rare earth zirconate at high temperatures, and can effectively increase the strain damage tolerance of the coating system, and effectively improve the thermal cycle life of the coating system;
[0027] 3. RE2(Zr 1-x Y x)2O7 has good high temperature phase stability and low thermal conductivity in the range of room temperature to 1600℃, and also has excellent corrosion resistance to molten salts such as CMAS;
[0028] 4. The novel composite rare earth silicate / rare earth zirconate gradient structure ultra-high temperature thermal / environmental barrier coating of the present invention has good resistance to high temperature water oxygen corrosion and sintering, and excellent high temperature interface stability. More importantly, the service temperature of the gradient structure ultra-high temperature thermal / environmental barrier coating of the present invention can reach 1400℃-1600℃, which effectively solves the problem of low temperature bearing of Si bonding layer. In addition, the gradient structure ultra-high temperature thermal / environmental barrier coating of the present invention has good high temperature structural stability;
[0029] 5. The gradient structure design of the ultra-high temperature thermal / environmental barrier coating system of the present invention: on the one hand, it alleviates the problem of thermal expansion mismatch between layers in the multi-layer coating system, so that the coating system of the present invention has a higher thermal cycle service life; on the other hand, it makes the coating system of the present invention have better resistance to high temperature water oxygen corrosion and molten salt corrosion;
[0030] 6. The present invention is a multi-layer ultra-high temperature protective coating system. The thickness of each layer cannot be too thick and must be controlled within a certain thickness range, otherwise the entire coating system will fail prematurely during service. If the thickness of each layer is too thin, it will not play the corresponding gradient transition and heat insulation role; if the thickness of each layer is too thick, it will also increase the thermal stress of the entire coating system, and the interlayer stress will also increase, resulting in a decrease in service life at ultra-high temperatures. Therefore, the thickness of each layer in the multi-layer ultra-high temperature coating system of the present invention is controlled within a certain range, and combined with appropriate spraying process parameters, a high-performance ultra-high temperature thermal / environmental barrier coating system is obtained;
[0031] 7. The gradient structure ultra-high temperature thermal / environmental barrier coating in the present invention is prepared by atmospheric plasma spraying technology, which has the advantages of simple operation, easy thickness control, high efficiency and low cost. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 It is a schematic structural diagram of the novel composite rare earth silicate / rare earth zirconate gradient structure ultra-high temperature thermal / environmental barrier coating of the present invention;
[0033] Figure 2 For the "SiC f / SiC ceramic matrix composite material matrix / Si / Yb2Si2O7 / Yb2Si2O7-Yb2SiO5 / La2(Zr 0.9 Y 0.1 )2O7" new gradient structure ultra-high temperature thermal / environmental barrier coating before 2000 thermal shocks at 1500℃;
[0034] Figure 3 For the "SiC f / SiC ceramic matrix composite material matrix / Si / Yb2Si2O7 / Yb2Si2O7-Yb2SiO5 / La2(Zr 0.9 Y 0.1 )2O7" new gradient structure ultra-high temperature thermal / environmental barrier coating after 2000 thermal shocks at 1500℃;
[0035] Figure 4 The "SiC" prepared in Example 3 f / SiC ceramic matrix composite material matrix / Si / Lu2Si2O7 / Lu2Si2O7-Yb2SiO5 / Sm2(Zr 0.95 Y 0.05 )2O7” new gradient structure ultra-high temperature thermal / environmental barrier coating cross-sectional morphology;
[0036] Figure 5 Sm2(Zr 0.95 Y 0.05 )2O7 top thermal insulation layer after CMAS+NaVO3 corrosion at 1450℃ for 1h and the corresponding surface distribution of Ca and Si elements;
[0037] Figure 6 Sm2(Zr 0.95 Y 0.05 )2O7 top thermal insulation layer after CMAS+NaVO3 corrosion for 4h at 1450℃ and the corresponding surface distribution of Ca and Si elements;
[0038] Figure 7 Sm2(Zr 0.95 Y 0.05 )2O7 top thermal insulation layer after CMAS+NaVO3 corrosion for 10h at 1450℃ and the corresponding surface distribution of Ca and Si elements;
[0039] Figure 8 Sm2(Zr 0.95 Y 0.05 )2O7 top insulation layer after CMAS+NaVO3 corrosion for 20h at 1450℃ and the corresponding surface distribution of Ca and Si elements;
[0040] Fig. 9 Sm2(Zr) sintered at 1500℃ for 100h 0.95 Y 0.05 )DSC-TG curve of the top thermal insulation layer of 2O7 from room temperature to 1500℃;
[0041] Fig.10After sintering at 1500℃ for 100h, Sm2(Zr 0.95 Y 0.05 )2O7 top thermal insulation layer DSC-TG curves from room temperature to 1500℃.
[0042] Fig.11 The prepared "Si / Yb2Si2O7 / La2(Zr 0.9 Y 0.1 )2O7” ultra-high temperature thermal / environmental barrier coating cross-sectional morphology;
[0043] Fig.12 The prepared "Si / Yb2Si2O7 / La2(Zr 0.9 Y 0.1 )2O7” ultra-high temperature thermal / environmental barrier coating after 10 thermal shocks at 1500℃. DETAILED DESCRIPTION
[0044] The above and other technical features and advantages of the present invention are described in more detail below in conjunction with the accompanying drawings.
[0045] The structure of the novel composite rare earth silicate / rare earth zirconate gradient structure ultra-high temperature thermal / environmental barrier coating obtained in Examples 1-3 is as follows: Figure 1 shown.
[0046] Example 1
[0047] The new composite rare earth silicate / rare earth zirconate gradient structure ultra-high temperature thermal / environmental barrier coating system is: SiC f / SiC ceramic matrix composite material matrix / Si / Yb2Si2O7 / Yb2Si2O7-Yb2SiO5 / La2(Zr 0.9 Y 0.1 )2O7;
[0048] In this embodiment, "SiC f / SiC ceramic matrix composite material matrix / Si / Yb2Si2O7 / Yb2Si2O7-Yb2SiO5 / La2(Zr 0.9 Y 0.1 The specific preparation steps of the new gradient structure ultra-high temperature thermal / environmental barrier coating of )2O7" are as follows:
[0049] (1) SiC f The SiC ceramic matrix composite material substrate is cleaned with alcohol and acetone to remove oil stains on the substrate surface, and then 24-mesh silicon carbide sand is used for sandblasting to increase the roughness of the composite material substrate surface, so as to improve the bonding strength of the coating system; acetone and anhydrous ethanol are used as media in turn, and the substrate after sandblasting is cleaned by ultrasonic vibration to remove the sand particles remaining on the substrate;
[0050] (2) A 45 μm thick Si bonding layer was first prepared on the surface of the roughened ceramic matrix composite material by atmospheric plasma spraying (APS). The particle size of the Si spraying powder used was between 30 and 65 μm. The process parameters for preparing the Si bonding layer by APS were as follows: spraying current of 550 A, spraying power of 32 kW, powder feeding rate of 15 g / min, spraying distance of 120 mm, main gas flow rate of Ar gas of 40 L / min, hydrogen flow rate of 2.5 L / min, spray gun moving speed of 600 mm / s, and step distance of 3 mm.
[0051] (3) Subsequently, the atmospheric plasma spraying technology was continued to be used to prepare a Yb2Si2O7 intermediate layer with a thickness of 60 μm on the substrate sprayed with the Si bonding layer. The spray powder material for preparing the Yb2Si2O7 intermediate layer by plasma spraying technology was 0.8Yb2Si2O7-0.2SiO2 (mol%), and the particle size of the 0.8Yb2Si2O7-0.2SiO2 composite agglomerated spray powder material was between 15-60μm. The process parameters for APS preparation of the Yb2Si2O7 intermediate layer were: spraying current of 600 A, spraying power of 40 kW, powder feeding rate of 30 g / min, spraying distance of 110 mm, main gas flow rate of Ar gas of 45 L / min, hydrogen flow rate of 6.5 L / min, spray gun moving speed of 500 mm / s, and step distance of 3 mm;
[0052] (4) On the surface of the substrate sprayed with Si bonding layer and Yb2Si2O7 intermediate layer, atmospheric plasma spraying technology was continued to be used to prepare a Yb2SiO5-Yb2Si2O7 transition layer with a thickness of 60 μm. The spray powder material for preparing the transition layer by plasma spraying technology was 0.5Yb2Si2O7-0.5Yb2SiO5, and the particle size of the Yb2SiO5-Yb2Si2O7 composite agglomerated spray powder material was between 15-60 μm. The process parameters for APS preparation of the Yb2SiO5-Yb2Si2O7 transition layer were: spraying current of 600A, spraying power of 40 kW, powder feeding rate of 25 g / min, spraying distance of 110 mm, main gas flow rate of Ar gas of 45 L / min, hydrogen flow rate of 6.5 L / min, spray gun moving speed of 500 mm / s, and step distance of 3 mm;
[0053] (5) Finally, the La2(Zr 0.9 Y 0.1 )2O7 top insulation layer, plasma spraying technology to prepare La2(Zr 0.9 Y0.1 )2O7 The particle size of the spray powder material of the top insulation layer is between 15-60 μm. 0.9 Y 0.1 The specific parameters of the top thermal insulation layer of )2O7 include: plasma spraying power 40 kW, spraying distance 90 mm, powder feeding rate 25 g / min, current 600 A, argon flow rate 35 L / min, hydrogen flow rate 5.5 L / min, and spray gun moving speed 500 mm / s.
[0054] Finally, atmospheric plasma spraying technology was used to produce La2(Zr 0.9 Y 0.1 )2O7 / Yb2SiO5-Yb2Si2O7 / Yb2Si2O7 / Si / ceramic matrix composite matrix with a novel gradient structure ultra-high temperature thermal / environmental barrier coating.
[0055] Figure 2 and Figure 3 This is a macroscopic morphology of the ultra-high temperature thermal / environmental barrier coating in this embodiment before and after 2000 thermal cycles of thermal shock at 1500°C. The ultra-high temperature thermal / environmental barrier coating system remains intact after 2000 thermal cycles at 1500°C, maintaining good high temperature structural stability.
[0056] The Yb2Si2O7 intermediate layer in this embodiment is calculated through Rietveld structure refinement, and it is found that the Yb2Si2O7 intermediate layer is composed of 99.6 mol% Yb2Si2O7 phase and 0.4 mol% Yb2SiO5 phase.
[0057] Example 2
[0058] The new composite rare earth silicate / rare earth zirconate gradient structure ultra-high temperature thermal / environmental barrier coating system is: SiC f / SiC ceramic matrix composite material matrix / Si / (Yb 0.5 Lu 0.5 )2Si2O7 / (Yb 0.5 Lu 0.5 )2Si2O7-(Yb 0.5 Lu 0.5 )2SiO5 / Sm2(Zr 0.95 Y 0.05 )2O7;
[0059] In this embodiment, "SiC f / SiC ceramic matrix composite material matrix / Si / (Yb 0.5 Lu 0.5 )2Si2O7 / (Yb 0.5 Lu 0.5)2Si2O7-(Yb 0.5 Lu 0.5 )2SiO5 / Sm2(Zr 0.95 Y 0.05 The specific preparation steps of the new gradient structure ultra-high temperature thermal / environmental barrier coating of )2O7" are as follows:
[0060] (1) SiC f The SiC ceramic matrix composite material substrate is cleaned with alcohol and acetone to remove oil stains on the substrate surface, and then 24-mesh silicon carbide sand is used for sandblasting to increase the roughness of the composite material substrate surface, so as to improve the bonding strength of the coating system; acetone and anhydrous ethanol are used as media in turn, and the substrate after sandblasting is cleaned by ultrasonic vibration to remove the sand particles remaining on the substrate;
[0061] (2) A Si bonding layer with a thickness of 60 μm was first prepared on the surface of the roughened ceramic-based composite material matrix by atmospheric plasma spraying (APS). The particle size of the Si spraying powder used was between 60 and 80 μm. The process parameters for preparing the Si bonding layer by APS were as follows: spraying current of 600 A, spraying power of 35 kW, powder feeding rate of 12 g / min, spraying distance of 100 mm, main gas flow rate of Ar gas of 35 L / min, hydrogen flow rate of 2.8 L / min, spray gun moving speed of 600 mm / s, and step distance of 3 mm.
[0062] (3) Subsequently, atmospheric plasma spraying technology was used to prepare 80 μm thick (Yb 0.5 Lu 0.5 )2Si2O7 intermediate layer, prepared by plasma spraying technology (Yb 0.5 Lu 0.5 )2Si2O7 intermediate layer spray powder material is 0.85(Yb 0.5 Lu 0.5 )2Si2O7-0.15SiO2 (mol%), 0.85(Yb 0.5 Lu 0.5 )2Si2O7-0.15SiO2 composite agglomerated spray powder material has a particle size between 15-60 μm. APS preparation (Yb 0.5 Lu 0.5 The process parameters of the 2Si2O7 intermediate layer are as follows: spraying current 500 A, spraying power 40 kW, powder feeding rate 25 g / min, spraying distance 120 mm, main gas flow rate Ar gas 40 L / min, hydrogen flow rate 6.8 L / min, spray gun moving speed 500 mm / s, step distance 3 mm;
[0063] (4) After spraying with Si bonding layer and (Yb0.5 Lu 0.5 )2Si2O7 intermediate layer was further coated with 80 μm thick (Yb 0.5 Lu 0.5 )2SiO5-(Yb 0.5 Lu 0.5 )2Si2O7 transition layer, the spray powder material of the transition layer prepared by plasma spraying technology is 0.6(Yb 0.5 Lu 0.5 )2Si2O7-0.4(Yb 0.5 Lu 0.5 )2SiO5,(Yb 0.5 Lu 0.5 )2SiO5-(Yb 0.5 Lu 0.5 )2Si2O7 composite agglomerated spray powder material has a particle size between 15-60 μm. 0.5 Lu 0.5 )2SiO5-(Yb 0.5 Lu 0.5 The process parameters of 2Si2O7 transition layer are as follows: spraying current 500 A, spraying power 40 kW, powder feeding rate 25 g / min, spraying distance 120 mm, main gas flow rate Ar gas 40 L / min, hydrogen flow rate 6.7 L / min, spray gun moving speed 500 mm / s, step distance 3 mm;
[0064] (5) Finally, spray with (Yb 0.5 Lu 0.5 )2SiO5-(Yb 0.5 Lu 0.5 )2Si2O7 / (Yb 0.5 Lu 0.5 )2Si2O7 / Si coating was further prepared on the substrate surface by atmospheric plasma spraying technology with a thickness of 150 μm. 0.95 Y 0.05 )2O7 top insulation layer, plasma spraying technology to prepare Sm2(Zr 0.95 Y 0.05 )2O7 The particle size of the spray powder material of the top insulation layer is between 15-60 μm. 0.95 Y 0.05 The specific parameters of the top thermal insulation layer of )2O7 include: plasma spraying power 40 kW, spraying distance 90 mm, powder feeding rate 25 g / min, current 600 A, argon flow rate 40 L / min, hydrogen flow rate 5.3 L / min, and spray gun moving speed 500 mm / s.
[0065] Finally, atmospheric plasma spraying technology was used to produce Sm2(Zr 0.95 Y 0.05 )2O7 / (Yb 0.5 Lu 0.5 )2SiO5-(Yb 0.5 Lu 0.5 )2Si2O7 / (Yb 0.5 Lu 0.5 )A novel gradient structure ultra-high temperature thermal / environmental barrier coating based on 2Si2O7 / Si / ceramic matrix composite matrix.
[0066] Example 3
[0067] The new composite rare earth silicate / rare earth zirconate gradient structure ultra-high temperature thermal / environmental barrier coating system is: SiC f / SiC ceramic matrix composite material matrix / Si / Lu2Si2O7 / Lu2Si2O7-Yb2SiO5 / Sm2(Zr 0.95 Y 0.05 )2O7;
[0068] In this embodiment, "SiC f / SiC ceramic matrix composite material matrix / Si / Lu2Si2O7 / Lu2Si2O7-Yb2SiO5 / Sm2(Zr 0.95 Y 0.05 The specific preparation steps of the new gradient structure ultra-high temperature thermal / environmental barrier coating of )2O7" are as follows:
[0069] (1) SiC f The SiC ceramic matrix composite material substrate is cleaned with alcohol and acetone to remove oil stains on the substrate surface, and then 24-mesh silicon carbide sand is used for sandblasting to increase the roughness of the composite material substrate surface, so as to improve the bonding strength of the coating system; acetone and anhydrous ethanol are used as media in turn, and the substrate after sandblasting is cleaned by ultrasonic vibration to remove the sand particles remaining on the substrate;
[0070] (2) A 55 μm thick Si bonding layer was first prepared on the surface of the roughened ceramic matrix composite material by atmospheric plasma spraying (APS). The particle size of the Si spraying powder used was between 45 and 70 μm. The process parameters for preparing the Si bonding layer by APS were as follows: spraying current of 550 A, spraying power of 30 kW, powder feeding rate of 10 g / min, spraying distance of 95 mm, main gas flow rate of Ar gas of 35 L / min, hydrogen flow rate of 2.6 L / min, spray gun moving speed of 550 mm / s, and step distance of 3 mm.
[0071] (3) Subsequently, the atmospheric plasma spraying technology was used to prepare a Lu2Si2O7 intermediate layer with a thickness of 80 μm on the substrate sprayed with the Si bonding layer. The spray powder material for the Lu2Si2O7 intermediate layer prepared by the plasma spraying technology was 0.84Lu2Si2O7-0.16SiO2 (mol%), and the particle size of the 0.84Lu2Si2O7-0.16SiO2 composite agglomerated spray powder material was between 15 and 60 μm. The process parameters for the APS preparation of the Lu2Si2O7 intermediate layer were: spraying current of 550 A, spraying power of 36 kW, powder feeding rate of 30 g / min, spraying distance of 100 mm, main gas flow rate of Ar gas of 45 L / min, hydrogen flow rate of 6.9 L / min, spray gun moving speed of 500 mm / s, and step distance of 3 mm;
[0072] (4) On the surface of the substrate sprayed with Si bonding layer and Lu2Si2O7 intermediate layer, atmospheric plasma spraying technology was continued to be used to prepare a Yb2SiO5-Lu2Si2O7 transition layer with a thickness of 60 μm. The spray powder material for preparing the transition layer by plasma spraying technology was 0.6Lu2Si2O7-0.4Yb2SiO5, and the particle size of the Yb2SiO5-Lu2Si2O7 composite agglomerated spray powder material was between 15-60 μm. The process parameters for APS preparation of the Yb2SiO5-Lu2Si2O7 transition layer were: spraying current of 500 A, spraying power of 36 kW, powder feeding rate of 25 g / min, spraying distance of 100 mm, main gas flow rate of Ar gas of 35 L / min, hydrogen flow rate of 6.5 L / min, spray gun moving speed of 500 mm / s, and step distance of 3 mm;
[0073] (5) Finally, Sm2(Zr 0.95 Y 0.05 )2O7 top insulation layer, plasma spraying technology to prepare Sm2(Zr 0.95 Y 0.05 )2O7 The particle size of the spray powder material of the top insulation layer is between 15-60 μm. 0.95 Y 0.05 The specific parameters of the top thermal insulation layer of )2O7 include: plasma spraying power 40 kW, spraying distance 90 mm, powder feeding rate 25 g / min, current 600 A, argon flow rate 40 L / min, hydrogen flow rate 5.3 L / min, and spray gun moving speed 500 mm / s.
[0074] Finally, atmospheric plasma spraying technology was used to produce Sm2(Zr 0.95 Y 0.05 )2O7 / Yb2SiO5-Lu2Si2O7 / Lu2Si2O7 / Si / ceramic matrix composite matrix based on a novel gradient structure ultra-high temperature thermal / environmental barrier coating.
[0075] Figure 4 The Si / Lu2Si2O7 / Lu2Si2O7-Yb2SiO5 / Sm2(Zr 0.95 Y 0.05 )2O7 gradient structure ultra-high temperature thermal / environmental barrier coating cross-sectional morphology. The layers in the gradient structure thermal / environmental barrier coating system are tightly bonded, no delamination occurs, and no large through-going longitudinal cracks are observed in the coating cross section. At the same time, Figure 5~Figure 8 Sm2(Zr 0.95 Y 0.05 )2O7 cross-sectional microstructure of the top thermal insulation layer after CMAS+NaVO3 corrosion at 1450℃ for different times. It can be observed from the figure that a relatively dense reaction layer is formed on the coating surface after 1 h of molten CMAS+NaVO3 corrosion at 1450℃. As the molten CMAS+NaVO3 corrosion time increases to 4 h, the thickness of the reaction layer increases. However, as the CMAS+NaVO3 corrosion time further increases to 10 h and 20 h, the thickness of the reaction layer remains unchanged, and the reaction layer becomes denser after 10 h of corrosion, becoming an effective barrier to further corrosion of molten salt. Sm2(Zr 0.95 Y 0.05 )2O7 top thermal insulation layer has the ability to resist CMAS / CMAS+NaVO3 joint corrosion at 1450℃. Fig. 9 As-prepared Sm2(Zr 0.95 Y 0.05 )2O7 top insulation layer from room temperature to 1500℃. It can be seen from the figure that there is no weight change during the heating process, and no endothermic peak or exothermic peak is found, indicating that Sm2(Zr 0.95 Y 0.05 )2O7 top insulation layer has excellent high temperature phase stability from room temperature to 1500℃; Fig.10 Sm2(Zr 0.95 Y 0.05 )2O7 top thermal insulation layer after sintering at 1500℃ for 100h. It can be seen from the figure that the coating has no weight change after sintering at 1500℃ for 100h, and no endothermic peak or exothermic peak is found, which further proves that Sm2(Zr 0.95 Y 0.05)2O7 top thermal insulation layer has excellent high temperature phase stability from room temperature to 1500℃.
[0076] Example 4
[0077] In SiC f The ultra-high temperature thermal / environmental barrier coating system on the surface of SiC ceramic matrix composite material is f / SiC ceramic matrix composites / Si / Yb2Si2O7 / La2(Zr 0.9 Y 0.1 )2O7;
[0078] In this embodiment, "SiC f / SiC ceramic matrix composite material matrix / Si / Yb2Si2O7 / La2(Zr 0.9 Y 0.1 The specific preparation steps of the )2O7" ultra-high temperature thermal / environmental barrier coating are as follows:
[0079] (1) The SiCf / SiC ceramic matrix composite substrate was cleaned with alcohol and acetone to remove oil stains on the substrate surface, and then 24-mesh silicon carbide sand was used for sandblasting to increase the roughness of the composite substrate surface, so as to improve the bonding strength of the coating system; acetone and anhydrous ethanol were used as the medium, and the substrate after sandblasting was cleaned by ultrasonic vibration to remove the sand particles remaining on the substrate;
[0080] (2) A Si bonding layer with a thickness of 45 μm was first prepared on the surface of the roughened ceramic-based composite material matrix by atmospheric plasma spraying (APS). The particle size of the Si spraying powder used was between 30 and 65 μm. The process parameters for preparing the Si bonding layer by APS were as follows: spraying current of 550 A, spraying power of 32 kW, powder feeding rate of 15 g / min, spraying distance of 120 mm, main gas flow rate of Ar gas of 40 L / min, hydrogen flow rate of 2.5 L / min, spray gun moving speed of 600 mm / s, and step distance of 3 mm.
[0081] (3) Subsequently, the atmospheric plasma spraying technology was used to prepare a Yb2Si2O7 intermediate layer with a thickness of 60 μm on the substrate sprayed with the Si bonding layer. The spray powder material of the Yb2Si2O7 intermediate layer prepared by the plasma spraying technology was a single-phase Yb2Si2O7 agglomerated spray powder material with a particle size between 15 and 60 μm. The process parameters for APS preparation of the Yb2Si2O7 intermediate layer were: spray current of 600 A, spray power of 40 kW, powder feeding rate of 30 g / min, spray distance of 110 mm, main gas flow rate of Ar gas of 45 L / min, hydrogen flow rate of 6.5 L / min, spray gun movement rate of 500 mm / s, and step distance of 3 mm;
[0082] (4) On the surface of the Si bonding layer and Yb2Si2O7 intermediate layer, the atmospheric plasma spraying technology was continued to prepare La2(Zr 0.9 Y 0.1 )2O7 top insulation layer, plasma spraying technology to prepare La2(Zr 0.9 Y 0.1 )2O7 The particle size of the spray powder material of the top insulation layer is between 15-60 μm. 0.9 Y 0.1 The specific parameters of the top thermal insulation layer of )2O7 include: plasma spraying power 40 kW, spraying distance 90 mm, powder feeding rate 25 g / min, current 600 A, argon flow rate 35 L / min, hydrogen flow rate 5.5 L / min, and spray gun moving speed 500 mm / s.
[0083] Finally, La2(Zr 0.9 Y 0.1 )2O7 / Yb2Si2O7 / Si / SiCf / SiC ceramic matrix composites for ultra-high temperature thermal / environmental barrier coatings.
[0084] The difference between Example 4 and Example 1 is that:
[0085] 1. The composition of the spray powder for preparing the Yb2Si2O7 intermediate layer in Example 4 is inconsistent. Example 4 uses a single-phase Yb2Si2O7 agglomerated spray powder material with a particle size between 15-60μm; while the spray powder for preparing the Yb2Si2O7 intermediate layer in Example 1 is a 0.8Yb2Si2O7-0.2SiO2 (mol%) composite agglomerated spray powder material with a particle size between 15-60μm. According to the XRD analysis results of the prepared Yb2Si2O7 intermediate layer after complete annealing and crystallization, the Rietveld structure refinement calculation showed that the Yb2Si2O7 intermediate layer in Example 4 was mainly composed of 75 mol% Yb2Si2O7 phase and 25 mol% Yb2SiO5 phase; and the Yb2Si2O7 intermediate layer in Example 1 was composed of 99.6 mol% Yb2Si2O7 phase and only 0.4 mol% Yb2SiO5 phase through Rietveld structure refinement calculation.
[0086] 2. The "SiC" prepared in Example 4 f / SiC ceramic matrix composite material matrix / Si / Yb2Si2O7 / La2(Zr 0.9 Y 0.1)2O7” ultra-high temperature thermal / environmental barrier coating does not contain a Yb2Si2O7-Yb2SiO5 transition layer. Fig.11 The prepared "Si / Yb2Si2O7 / La2(Zr 0.9 Y 0.1 )2O7" ultra-high temperature thermal / environmental barrier coating cross-sectional morphology. It can be seen from the figure that Si / Yb2Si2O7 / La2(Zr 0.9 Y 0.1 )2O7 ultra-high temperature thermal / environmental barrier coating system is relatively dense, with the top layer La2(Zr 0.9 Y 0.1 )2O7, there are a few longitudinal cracks only inside the top layer but do not extend to the Yb2Si2O7 middle layer.
[0087] Example 4 "SiC f / SiC ceramic matrix composite material matrix / Si / Yb2Si2O7 / La2(Zr 0.9 Y 0.1 )2O7" ultra-high temperature thermal / environmental barrier coating system was heat treated at 1400℃ for 10h on the top layer La2(Zr 0.9 Y 0.1 )2O7, and as the heat treatment time increases, the longitudinal cracks continue to expand into the Yb2Si2O7 intermediate layer. At the same time, after heat treatment at 1400℃ for 10h, a new layer of Yb2Si2O7 phase is generated at the interface between Si and Yb2Si2O7 layers. The ultra-high temperature thermal / environmental barrier coating in Example 4 exhibited obvious spalling failure after only 10 cycles of thermal shock at 1500℃. Fig.12 The prepared "Si / Yb2Si2O7 / La2(Zr 0.9 Y 0.1 )2O7" ultra-high temperature thermal / environmental barrier coating after 10 thermal shocks at 1500℃. It can be seen from the figure that the entire thermal / environmental barrier coating system has failed due to peeling, and there are obvious large longitudinal cracks penetrating into the Si bonding layer. At the same time, the Si bonding layer has undergone significant thermal expansion, which is mainly due to the Yb2Si2O7 / La2(Zr 0.9 Y 0.1 )2O7 thermal expansion mismatch leads to the generation of large longitudinal cracks during the heating and cooling cycle. As the number of thermal cycles increases, the cracks extend to the Si bonding layer. At the same time, the Si bonding layer is exposed to a high temperature of 1500°C, causing Si to melt and expand due to the heat, ultimately leading to the failure of the entire thermal / environmental barrier coating system.
[0088] The above description is only a preferred embodiment of the present invention, which is only illustrative and not restrictive of the present invention. Those skilled in the art understand that many changes, modifications, and even equivalences may be made to the present invention within the spirit and scope defined by the claims of the present invention, but all of them will fall within the scope of protection of the present invention.
Claims
1. A composite rare earth silicate-rare earth zirconate gradient structure ultra-high temperature thermal / environmental barrier coating, characterized in that: It includes a Si bonding layer, a RE2Si2O7 intermediate layer, a RE2SiO5-RE2Si2O7 composite rare earth silicate transition layer, and a rare earth zirconate thermal insulation top layer, which are sequentially prepared on a ceramic-based composite material substrate; The rare earth RE in the RE2Si2O7 intermediate layer is any one of ytterbium and lutetium or a combination of the two, and the molar fraction of RE2Si2O7 is ≥97%; The rare earth RE in the RE2SiO5-RE2Si2O7 composite rare earth silicate transition layer is any one of ytterbium and lutetium or a combination of the two, and the molar ratio of RE2SiO5 to RE2Si2O7 in the RE2SiO5-RE2Si2O7 coating system is 0.67-1.5; The rare earth zirconate thermal insulation top layer is RE2 (Zr 1-x Y x )2O7, wherein RE is lanthanum or samarium, 0≤x≤0.
1.
2. The composite rare earth silicate-rare earth zirconate gradient structure ultra-high temperature thermal / environmental barrier coating according to claim 1, characterized in that: The matrix of the ceramic-based composite material is a silicon carbide fiber reinforced silicon carbide ceramic matrix or a carbon fiber reinforced silicon carbide ceramic matrix.
3. A method for preparing the composite rare earth silicate-rare earth zirconate gradient structure ultra-high temperature thermal / environmental barrier coating according to claim 1 or 2, characterized in that: The following steps are involved: S1, cleaning the ceramic matrix composite material substrate with alcohol and acetone to remove oil stains on the substrate surface, roughening the substrate with 24-mesh silicon carbide sand blasting, and cleaning the roughened substrate with acetone and anhydrous ethanol as the medium by ultrasonic vibration to remove the sand remaining on the substrate; S2, using atmospheric plasma spraying technology to prepare a Si bonding layer on the surface of the ceramic-based composite material substrate roughened in step S1, wherein the thickness of the Si bonding layer is 40-80 μm, and the particle size of the Si spraying powder used is 30-90 μm; S3, after the substrate on which the Si bonding layer is sprayed is further coated, an atmospheric plasma spraying technology is used to prepare a RE2Si2O7 intermediate layer, the thickness of which is 50-100 μm. The spraying powder material of the RE2Si2O7 intermediate layer prepared by the plasma spraying technology is (1-x)RE2Si2O7-xSiO2, wherein 0.05≤x≤0.2, and the particle size of the (1-x)RE2Si2O7-xSiO2 composite agglomerated spraying powder material is 15-60 μm; S4, on the substrate surface sprayed with Si bonding layer and RE2Si2O7 intermediate layer, atmospheric plasma spraying technology is continued to be used to prepare RE2SiO5-RE2Si2O7 transition layer, the thickness of which is 50-80μm, the spraying powder material of the transition layer prepared by plasma spraying technology is (1-x)RE2Si2O7-xRE2SiO5, wherein 0.4≤x≤0.5, and the particle size of RE2SiO5-RE2Si2O7 composite agglomerated spraying powder material is 15-60μm; S5, on the surface of the substrate sprayed with RE2SiO5-RE2Si2O7 / RE2Si2O7 / Si coating, atmospheric plasma spraying technology is continued to be used to prepare RE2(Zr 1-x Y x )2O7 top insulation layer, the thickness of which is 100-150μm, and the plasma spraying technology is used to prepare RE2(Zr 1- x Y x )2O7 The particle size of the spray powder material of the top insulation layer is 15-60μm, and RE2(Zr 1-x Y x )2O7 / RE2SiO5-RE2Si2O7 / RE2Si2O7 / Si / ceramic matrix composite material matrix with a new gradient structure ultra-high temperature thermal / environmental barrier coating.
4. The method for preparing a composite rare earth silicate-rare earth zirconate gradient structure ultra-high temperature thermal / environmental barrier coating according to claim 3, characterized in that: In the step S2, the process parameters for preparing the Si bonding layer by atmospheric plasma spraying technology are: spraying current is 500-650A, spraying power is 30-35kW, powder feeding rate is 10-35g / min, spraying distance is 90-120mm, main gas flow rate Ar gas is 32-45L / min, hydrogen flow rate is 2-10L / min, spray gun moving speed is 500-650mm / s, and step distance is 3mm.
5. The method for preparing a composite rare earth silicate-rare earth zirconate gradient structure ultra-high temperature thermal / environmental barrier coating according to claim 3, characterized in that: In step S3, the process parameters for preparing the RE2Si2O7 intermediate layer by atmospheric plasma spraying technology are: spraying current is 500-600A, spraying power is 34-42kW, powder feeding rate is 20-40g / min, spraying distance is 90-120mm, main gas flow rate Ar gas is 32-45L / min, hydrogen flow rate is 2-12L / min, spray gun moving speed is 500-650mm / s, and step distance is 3mm.
6. The method for preparing a composite rare earth silicate-rare earth zirconate gradient structure ultra-high temperature thermal / environmental barrier coating according to claim 3, characterized in that: In step S4, the process parameters for preparing the RE2SiO5-RE2Si2O7 transition layer by atmospheric plasma spraying technology are: spraying current is 500-600A, spraying power is 34-42kW, powder feeding rate is 20-40g / min, spraying distance is 90-120mm, main gas flow rate Ar gas is 32-45L / min, hydrogen flow rate is 2-12L / min, spray gun moving speed is 500-650mm / s, and step distance is 3mm.
7. The method for preparing a composite rare earth silicate-rare earth zirconate gradient structure ultra-high temperature thermal / environmental barrier coating according to claim 3, characterized in that: In step S5, the atmospheric plasma spraying technology is used to prepare RE2 (Zr 1-x Y x )The process parameters of the top thermal insulation layer of 2O7 are: plasma spraying power 35~45kW, spraying distance 85~110mm, powder feeding rate 20~40g / min, current 500~650A, argon flow rate 30~45L / min, hydrogen flow rate 4~10L / min, and spray gun moving speed 500~600mm / s.